Implementation of the Website on the Raudhatul Mukhlisin Mosque Fund, Sako District Using the Waterfal Method - Musmirul Gina Ikbal Gina; Kemas Muhammad Wahyu Hidayat; Karnadi (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2025)
Mosques play a central role in Muslim community life, not only as places of worship but also as centers for social and financial activities, such as donations, alms management, and dissemination of mosque-related information. However, in the current era of rapid technological development, many mosques still rely on manual systems for financial management and information delivery, which are prone to recording errors, calculation inaccuracies, data loss, and limited transparency. This condition can reduce public trust and hinder effective mosque management. Therefore, technological innovation is needed to support transparent, accurate, and efficient mosque administration. This research aims to assist the management of Raudhatul Mukhlisin Mosque in improving the efficiency and accuracy of mosque financial data management through the development of a website-based information system. The system was developed using the Waterfall method, which includes requirement analysis, system design, implementation, testing, and maintenance. This study applies qualitative research methods with data collection techniques including observation and literature review. The developed system utilizes PHP, HTML, and MySQL, and system testing was conducted using the Black Box method. The results show that the proposed system facilitates data recording, financial reporting, and information access, while enhancing transparency and accountability for mosque administrators and worshippers.